Branded Component Strategies Ingredient Branding in B2B Markets - Worm, Stefan. (Gabler Verlag : Imprint: Gabler Verlag, 2012)
In the quest for better differentiation of their products, many firms in B2B markets have started to systematically invest in brand building. Stefan Worm analyzes how component supplier brand strength among original equipment manufacturers’ (OEMs’) customers affects component suppliers’ market performance in their relationships with these OEMs. Further, the author determines which management instruments are effective in building, sustaining, and leveraging component supplier brand strength. The analysis relies on data collected from multiple manufacturing industries.